ICT at African Universities - Hoosen, Sarah; Butcher, Neil (International Higher Education, 2012)
Many African nations and regional bodies are recognizing the importance of Information and Communication Technology (ICT) in promoting social and economic change, generating both significant opportunities and challenges for African universities. This article focuses on experiences in the Partnership for Higher Education in Africa (PHEA) Educational Technology Initiative (ETI) to present a picture of what is taking place at African universities, providing examples of successes and failures and their wider implications for practitioners in the field of e-learning.